Algebra


  1. For what value of k, the system of equations
    5x + 2y = k
    10x + 4y = 3 has infinite solutions ?









  1. View Hint View Answer Discuss in Forum

    a1x + b1y + c1 = 0 and
    a2x + b2y + c2 = 0 will have infinite solutions if

    a1
    =
    b1
    =
    c1
    a2b2c2

    ⇒ 
    5
    =
    2
    =
    −k
    104−3

    ⇒ 
    1
    =
    k
    ⇒ k =
    3
    232

    Correct Option: A

    a1x + b1y + c1 = 0 and
    a2x + b2y + c2 = 0 will have infinite solutions if

    a1
    =
    b1
    =
    c1
    a2b2c2

    ⇒ 
    5
    =
    2
    =
    −k
    104−3

    ⇒ 
    1
    =
    k
    ⇒ k =
    3
    232


  1. If 4x2 + 4y2 + 4z2 = 12x + 12y – 18 then x + y + z = ?









  1. View Hint View Answer Discuss in Forum

    4x2 + 4y2 + 4z2 – 12x – 12y + 18 = 0
    ⇒  (2x)2 – 2 × 2x × 3 + 9 + (2y)2 – 2 × 2y × 3 + 9 + 4z2 = 0
    ⇒  (2x – 3)2 + (2y – 3)2 + 4z2 = 0
    ⇒  2x – 3 = 0

    ⇒  x =
    3
    ;
    2

    2y – 3 = 0
    ⇒  x =
    3
    , z = 0
    2

    =
    6
    = 3
    2

    [If x2 + y2 + z2 = 0 ⇒ x = 0, y = 0, z = 0]

    Correct Option: A

    4x2 + 4y2 + 4z2 – 12x – 12y + 18 = 0
    ⇒  (2x)2 – 2 × 2x × 3 + 9 + (2y)2 – 2 × 2y × 3 + 9 + 4z2 = 0
    ⇒  (2x – 3)2 + (2y – 3)2 + 4z2 = 0
    ⇒  2x – 3 = 0

    ⇒  x =
    3
    ;
    2

    2y – 3 = 0
    ⇒  x =
    3
    , z = 0
    2

    =
    6
    = 3
    2

    [If x2 + y2 + z2 = 0 ⇒ x = 0, y = 0, z = 0]



  1. What will be the value of (x – a)3 + (x – b)3 + (x – c)3 – 3 (x – a) (x – b) (x – c) if a + b+c = 3x ?









  1. View Hint View Answer Discuss in Forum

    x – a + x – b + x – c
    = 3x – (a + b + c) = 0
    ∴  (x – a)3 + (x – b)3 + (x – c)3 – 3
    (x – a) (x – b) (x – c) = 0
    [∵  a3 + b3 + c3– 3abc = 0 when a + b + c = 0]

    Correct Option: C

    x – a + x – b + x – c
    = 3x – (a + b + c) = 0
    ∴  (x – a)3 + (x – b)3 + (x – c)3 – 3
    (x – a) (x – b) (x – c) = 0
    [∵  a3 + b3 + c3– 3abc = 0 when a + b + c = 0]


  1. If a + b + c = 15 and a2 + b2 + c2 = 83, then a3 + b3 + c3 – 3abc = ?









  1. View Hint View Answer Discuss in Forum

    a3 + b3 + c3 – 3abc = (a + b + c)
    (a2 + b2 + c2 – ab – bc – ca)
    Now, (a + b + c)2 = a2 + b2 + c2 + 2 (ab + bc + ca)
    ⇒  152 = 83 + 2 (ab + bc + ca)
    ⇒  225 = 83 + 2 (ab + bc + ca)
    ⇒  142 = 2 (ab + bc + ca)

    ⇒  ab + bc + ca =
    142
    = 71
    2

    ∴  a3 + b3 + c3 – 3abc = 15 × (83 – 71) = 15 × 12 = 180

    Correct Option: C

    a3 + b3 + c3 – 3abc = (a + b + c)
    (a2 + b2 + c2 – ab – bc – ca)
    Now, (a + b + c)2 = a2 + b2 + c2 + 2 (ab + bc + ca)
    ⇒  152 = 83 + 2 (ab + bc + ca)
    ⇒  225 = 83 + 2 (ab + bc + ca)
    ⇒  142 = 2 (ab + bc + ca)

    ⇒  ab + bc + ca =
    142
    = 71
    2

    ∴  a3 + b3 + c3 – 3abc = 15 × (83 – 71) = 15 × 12 = 180



  1. For what value of ‘a’, the polynomial 2x3 + ax2 + 11x + a + 3, is exactly divisible by (2x – 1) ?









  1. View Hint View Answer Discuss in Forum

    Let, P(x) = 2x3 + ax2 + 11x + a + 3
    (2x – 1) is its factor.

    ∴  p
    1
    = 0
    2

    ⇒  2 ×
    1
    3 + a ×
    1
    2 + 11 ×
    1
    + a + 3 = 0
    222

    ⇒ 
    1
    +
    a
    +
    11
    + a + 3 = 0
    442

    ⇒ 
    1 + a + 22 + 4a + 12
    = 0
    4

    ⇒ 
    5a + 35
    = 0
    4

    ⇒  5a + 35 = 0 ⇒ 5a = – 35
    ⇒  a = –7

    Correct Option: B

    Let, P(x) = 2x3 + ax2 + 11x + a + 3
    (2x – 1) is its factor.

    ∴  p
    1
    = 0
    2

    ⇒  2 ×
    1
    3 + a ×
    1
    2 + 11 ×
    1
    + a + 3 = 0
    222

    ⇒ 
    1
    +
    a
    +
    11
    + a + 3 = 0
    442

    ⇒ 
    1 + a + 22 + 4a + 12
    = 0
    4

    ⇒ 
    5a + 35
    = 0
    4

    ⇒  5a + 35 = 0 ⇒ 5a = – 35
    ⇒  a = –7